1978
DOI: 10.1084/jem.148.1.335
|View full text |Cite
|
Sign up to set email alerts
|

Virus-induced atherosclerosis.

Abstract: Of four groups of chickens, two (groups I and II) were infected with MDV and two were not (groups III and IV). Groups I and III were fed diets low in lipid, and groups II and IV were fed cholesterol-supplemented diets. Striking grossly visible atherosclerotic lesions were seen in large coronary arteries, aortas, and major aortic branches of infected normocholesterolemic and hypercholesterolemic chickens (groups I and II). In contrast, grossly visible atherosclerotic lesions were not seen in uninfected normocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
185
0
18

Year Published

1986
1986
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(203 citation statements)
references
References 9 publications
0
185
0
18
Order By: Relevance
“…The ubiquity and the ability to cycle between dormancy and replication make HHVs candidates for the role of constant triggers of immunoactivation that is closely related to the development of atherosclerosis. Early in 1980s, it was shown in chickens infected with Marek disease herpesvirus12 that diet‐induced experimental atherosclerosis developed at a higher rate than in control animals. Evidence of the involvement of HHVs in the development of atherosclerosis and restenosis after coronary angioplasty and in the acceleration of atherosclerosis development in heart transplant recipients has also been reported 29.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ubiquity and the ability to cycle between dormancy and replication make HHVs candidates for the role of constant triggers of immunoactivation that is closely related to the development of atherosclerosis. Early in 1980s, it was shown in chickens infected with Marek disease herpesvirus12 that diet‐induced experimental atherosclerosis developed at a higher rate than in control animals. Evidence of the involvement of HHVs in the development of atherosclerosis and restenosis after coronary angioplasty and in the acceleration of atherosclerosis development in heart transplant recipients has also been reported 29.…”
Section: Discussionmentioning
confidence: 99%
“…Among known human viruses, human herpesviruses (HHVs) fit these criteria. Studies in animal models have demonstrated that HHVs are capable of contributing to the development of atherosclerosis‐type pathologies 12. Data on the involvement of HHVs in human atherosclerosis are far less conclusive13 and are predominantly based on epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%
“…An infectious etiology underlying atherosclerotic vascular disease has long been hypothesized (3,4). In the 1970s, arterial disease very similar to human atherosclerosis was induced by cytomegalovirus (CMV) infection in chickens.…”
mentioning
confidence: 99%
“…After the first report of an association of viral infection and atherosclerosis in 1970, 1 evidence is accumulating that infections are involved in the development and progression of atherosclerosis, with special focus on carotid and coronary lesions. 2,3 The pathogenetic mechanisms may vary and are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%